Informatively of metonymy in Arabic rhetoric lesson - Hussein Al-Khafaji, Zeena Ghani Abdul (Opción, 2019)
Textual science – as researchers and scholars see it – is one of the latest language science branches and is involved in the chain of subjective and methodological evolution. This science was established according to the works of a German group of researchers back in 1968 under the supervision of Hartmann and Weinrich, as Hartmann convened the first conference under his guidance to discuss text language and established a new lingual and textual research center later. These beginnings started to make progress in the seventies by (Van Djik) who called for the importance of this science provided that the grammatical description includes the relations between sentences on two levels: Superficial and profound. The dream of this matter has been realized by the American (Robert de Beaugrande) after laying seven standards for textuality, one of them is the informativity(1) as he classified them into two closely text-related standards which are (Cohesion and Coherence), two psychological standards (Situationality and Intertex- tuality); left the two standards related to the producer and recipient of the text which are (Intentionality and acceptability) without classification as well leaving the (informativity) for the perception of the producer and recipient(2). Researchers confirmed that there is a strong bond between textual science and rhetoric, as (Van Djik) saw that historical event of the textual science is clear through our careful examination of the general direction of old rhetoric which went to describe texts and their distinguished functions. Rhetoric is connected to particular stylistic forms and models, while (Harweg) saw that Rhetoric and stylistics are previous branches promising of textual science. Here comes the importance of the research entitled (informativity of meton- ymy in Arabic rhetoric lesson) in its attempt to uncover the high informative efficiency of metonymy based on what it conceals and contains in terms of meanings and images, therefore it has required two axes preceded by an intro- duction and followed by a conclusion that shows the important research result. The first axis is allocated to talk about the informative origins of Arabic rheto- ric and the other axis is allocated to discuss metonymy informativity.